2018
DOI: 10.3892/etm.2018.6628
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous kyphoplasty treatment evaluation for patients with K�mmell disease based on a two‑year follow‑up

Abstract: Percutaneous kyphoplasty (PKP) has been used in Kümmell disease treatment for years. The objective of the current study was to evaluate the efficacy and safety of PKP in the treatment of patients with Kümmell disease and to explore the association between cement injection volume and pain relief. A total of 50 patients were enrolled in the present study and follow-up was 2 years. Efficacy was evaluated using the Visual Analog Scale (VAS), the Oswestry Disability Index (ODI) and the kyphotic angle (Cobb's angle)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and at the same time partially restore the height of the vertebra and correct the kyphosis [11,[21][22][23][24][25][26][27][28]. During spinal flexion and extension, due to the presence of IVC and the formation of false joints, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and at the same time partially restore the height of the vertebra and correct the kyphosis [11,[21][22][23][24][25][26][27][28]. During spinal flexion and extension, due to the presence of IVC and the formation of false joints, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and partially restore the height of the vertebra and correct the kyphosis [11,[22][23][24][25][26][27][28][29]. During spinal flexion and extension, due to the presence of IVC and the formation of pseudojoint, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were following: (1) aged 60 years or older; (2) fragility fracture of thoracic or lumbar vertebra (without trauma or with minor trauma, as tumble or sprain); (3) underwent surgical intervention; (4) IVC in the vertebral body could be found by CT imaging; (5) complete radiological information including X-ray, CT, and MRI could be achieved. Exclusion criteria were following: (1) burst fracture of a thoracic and lumbar vertebra; (2) pathological fracture due to infection or malignancy; (3) with adjacent vertebral fractures; (4) incomplete radiological information; (5) younger than 60 years old; (6) cannot recall the details about the injury; (7) with no history of injury; (8) underwent conservative treatment. The study was approved by the institutional review board and the ethics committee of our hospital.…”
Section: Patient Populationmentioning
confidence: 99%